Digital business taxation issues and threats abstract - Gulbinas, Alanas; Jogminaitė, Kamilė (Vilnius University Open Series, 2020)
“Article of digital business taxation issues and threats”, analyzes the impact of the digitalization in modern society and the changes of corporate profit tax. This article has been concentrated on the regulation of the European Union but mentions the international adjustments as well. The article has been written in a discussion of national law and bilateral agreements, which apply to the traditional permanent headquarters concept. This article discusses the current situation, where digital businesses are not being taxed with corporate profit tax, and possibilities to change it according to the needs of the digital economy In addition, when digital businesses emerged, the permanent headquarters concept, which taxed based on the permanent location, required further discussion and a new definition. Therefore, the article talks over the proposals of the European Union to equalize corporate profit taxation. The article analyzes the possible consequences and issues of the adaptation of the EU directive. In question of regulating the corporate profit tax, the authors discussed the competence of the EU.
Keywords: none